Relationship between green or black tea consumption and cerebral stroke: A systematic review and meta-analysis - Moloud Fakhri; Tayebe Jamshidbeigi; Ayda Hasanpour Dehkordi; Mohsen Abdan; Sam Mirfendereski; Diana Sarokhani (Shahrekord University of Medical Sciences, 2024)
After water, tea is the most popular drink in the world, and its relationship with heart diseases, stroke, and cancer has been always considered by researchers. The aim of the present study is to assess the relationship between green tea or black tea consumption and stroke risk using systematic review and meta-analysis methods. To assess the required resources, PubMed, Scopus, Web of science, Cochrane electronic databases, and the Google Scholar search engine were searched. To assess the study heterogeneity, I2 indexes was used. Data were analyzed using STATA 14 software. P<0.05 was considered to be statistically significant. The preventive effect of green tea on cerebral stroke in the case-control studies was more than cohort studies and higher in women than men. Its effect was also lower in people who consume green tea more than 10 years in comparison to people who consume it less than 10 years. Green tea effect was higher in those who consume more than 5 cups/day than those with less than 5 cups/day. The effect of black tea consumption in men and in those who drank less than 5 cups a day or those who drink black tea for 10 years or more was estimated in preventive cohort studies. Green tea has a significant preventive effect on the risk of stroke in different doses and periods of consumption; however, black tea is preventive in a dose of fewer than 5 cups per day and for a period of more than 10 years.